Development of Interactive Teaching Materials for Excretory System Materials Using Smart Apps Creator - Jusman Tang; Fenny Hasanuddin (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to develop interactive teaching materials using valid Smart Apps Creator Apps. This type of research is research and development (Research and Development), while the procedure for implementing research follows the stages of the ADDIE development model, in research only to the third stage, namely the development stage (Development). The instrument used is a validation sheet for experts, which consists of a validation sheet for material experts and a validation sheet for media experts. The data analysis technique used is validity data analysis. The data is analyzed quantitatively. The results of the material expert validator assessment of interactive teaching materials using Smart Apps Creator Applications are in the valid category with an average validity of 4.5 and the results of the media expert validator assessment of teaching materials are in the average valid category of 4.5 validity. The assessment results of the two validators show that interactive teaching materials using Smart Apps Creator that were developed are suitable for use or implementation in class as one of the teaching materials.